An Algorithm for the Forward Position Kinematics of General Stewart Platform Mechanism - Wang Furong; Xin Jiaoli (Jixie chuandong)
A new algebra algorithm for the forward position kinematics of general Stewart platform（ GSP）is presented. First of all,the 20 original equations containing 9 variables are built according to the geometric construction of GSP. Then,the Groebner basis under the degree reverse lexicographic term ordering for the 20 equations is solved,and the 29 Groebner basis can be selected from it and compressing proper variable,the 2929 Sylvester matrix is constructed. A 40 th degree univariate equation is achieved from the determinate of the matrix. Finally,the total 40 solutions of the corresponding other variables can be obtained by back substitution method. A numerical example is deployed to verify the algorithm. The algorithm is also suitable for the forward position kinematics analysis of the other type of parallel- mechanism.